ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT PLN (PERSERO) ULP WAY HALIM - Baita Baita; Emi Sumarmi (Universitas Bina Taruna Gorontalo, 2024)
The purpose of this research was to analyze the effect of service quality on PT PLN (Persero) customers' levels of satisfaction. In this study, 160 PT PLN (Persero) ULP Way Halim customers participated in a survey using quantitative research methods. The independent variables in this research are Reliability (X1), Assurance (X2), Tangible (X3), Empathy (X4) and Responsiveness (X5) and the dependent variable in this research is Customer Satisfaction (Y). The calculation results of the Reliability variable (X1) obtained a t value of 2.744, the result of the Assurance variable (X2) was 1.002, the result of the Tangible variable (X3) was 1.442, the result of the Empathy (X4) variable was 2.205, and the result of the Responsiveness variable (X5) is 3.932, which shows that the variables Reliability (X1), Empathy (X4), and Responsiveness (X5) have a significant and influential effect on Customer Satisfaction (Y).